Modeling best practice life expectancy using gumbel autoregressive models - Anthony Medford (Risks, 2021)
Best practice life expectancy has recently been modeled using extreme value theory. In this paper we present the Gumbel autoregressive model of order one-Gumbel AR(1)-as an option for modeling best practice life expectancy. This class of model represents a neat and coherent framework for modeling time series extremes. The Gumbel distribution accounts for the extreme nature of best practice life expectancy, while the AR structure accounts for the temporal dependence in the time series. Model diagnostics and simulation results indicate that these models present a viable alternative to Gaussian AR(1) models when dealing with time series of extremes and merit further exploration.
Keywords: 330; autoregression; best practice life expectancy; extreme values; Gumbel models; time series